CVB3-Mediated Mitophagy Plays an Important Role in Viral Replication via Abrogation of Interferon Pathways - Oh, Soo-Jin; Lim, Byung-Kwan; Yun, Jeanho; Shin, Ok Sarah (Frontiers in Cellular and Infection Microbiology, 2021)
Coxsackievirus B3 (CVB3) is a common enterovirus that causes systemic inflammatory diseases, such as myocarditis, non-septic meningitis, and encephalitis. CVB3 has been demonstrated to subvert host cellular responses via autophagy to support viral replication in neural stem cells. Mitophagy, a specialized form of autophagy, contributes to mitochondrial quality control via degrading damaged mitochondria. Here, we show that CVB3 infection induces mitophagy in human neural progenitor cells, HeLa and H9C2 cardiomyocytes. In particular, CVB3 infection triggers mitochondrial fragmentation, loss of mitochondrial membrane potential, and Parkin/LC3 translocation to the mitochondria. Rapamycin or carbonyl cyanide m-chlorophenyl hydrazone (CCCP) treatment led to increased CVB3 RNA copy number in a dose-dependent manner, suggesting enhanced viral replication via autophagy/mitophagy activation, whereas knockdown of PTEN-induced putative kinase protein 1(PINK1) led to impaired mitophagy and subsequent reduction in viral replication. Furthermore, CCCP treatment inhibits the interaction between mitochondrial antiviral signaling protein (MAVS) and TANK-binding kinase 1(TBK1), thus contributing to the abrogation of type I and III interferon (IFN) production, suggesting that mitophagy is essential for the inhibition of interferon signaling. Our findings suggest that CVB3-mediated mitophagy suppresses IFN pathways by promoting fragmentation and subsequent sequestration of mitochondria by autophagosomes.